Development and initial validation of the Engagement in Athletic Training Scale - Liu, Jing-Dong; Wu, Jun-Xia; Zou, Yu-Duo; Wang, Zhong-Hao; Zhang, Shuge; Hu, Jin-Chuan; Liu, Hao (Frontiers in Psychology, 2024)
The current study presents the development process and initial validation of the engagement in athletic training scale (EATS), which was designed for evaluating athletes' engagement in athletic training. In Study 1, item generation and initial content validity of the EATS were achieved. In Study 2, the factor structure of the EATS was examined using the exploratory factor analysis (EFA) and exploratory structural equation modelling (ESEM). Internal consistency reliabilities of the subscales were examined (N=460). In Study 3, factor structure, discriminant validity, internal consistency reliability and nomological validity of the EATS were further examined in an independent sample (N=513). Meanwhile, measurement invariance of the EATS across samples (study 2 and study 3) and genders were evaluated. Overall, results from the three rigorous studies provided initial psychometric evidence for the 19-item EATS and suggested that the EATS could be used as a valid and reliable measure to evaluate athletes' engagement in athletic training.